Water Demand Analysis within the Pursat River Catchment - Hatfield Consultants; MOWRAM/DHRW Consultants (2013)
In order to address water resources issues and develop capacities for implementing IWRM, there is a need for better collaboration between sectors and use of scientific data in decision making. Collaborative and informed decision-making rely on better understanding of, and access to quantitative and qualitative research results. Multi-stakeholder Platforms (MSPs) are forums to share and discuss such research outputs with various government sectors and water users. This report contributes to the Stung Pursat MSP process by providing information about changes in water balance in Pursat. The objectives of the Water Demand Analysis within the Pursat River Catchment report are to:  Present and compare the water balance in the Pursat catchment under two scenarios; a) natural scenario (absence of Dam No. 1, No. 3, and No. 5) and b) dam scenario (presence of Dam 1, 3, and 5); and  Apply and critique the